2008
DOI: 10.1001/archpedi.162.7.627
|View full text |Cite
|
Sign up to set email alerts
|

Association of Infant Child Care With Infant Feeding Practices and Weight Gain Among US Infants

Abstract: Child care factors were associated with unfavorable infant feeding practices and more weight gain during the first year of life in a nationally representative cohort. The effects of early child care on breastfeeding and introduction of solid foods warrant longer follow-up to determine subsequent risk of childhood overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
115
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 32 publications
13
115
4
Order By: Relevance
“…Kim and Peterson (2008) also showed that infants in daycare gained more weight during the first 9 months compared to those in parental care. These findings may be explained by the lower rate of breast feeding and higher rate of early solid food introduction in infants in daycare.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kim and Peterson (2008) also showed that infants in daycare gained more weight during the first 9 months compared to those in parental care. These findings may be explained by the lower rate of breast feeding and higher rate of early solid food introduction in infants in daycare.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the rate of weight gain during early stages of infancy is considered a key predictor of future health conditions. Rapid weight gain in infancy is thought to be associated with maternal lifestyle and environmental factors (Ong et al 2000(Ong et al , 2002Kim and Peterson 2008). Presumably, controlling these factors should reduce the risk of adult chronic diseases.…”
mentioning
confidence: 99%
“…For breast-feeding at 12 months of age, we observed a significant negative association with nonparental day care and observed that infants who had non-parental care had lower odds of being breast-fed at this age. A recent study from the USA (24) , using a national representative sample of 8150 infants, reported that infants who attended day care before 3 months of age were less likely to ever have been breast-fed than those in parental care. In another national sample of 2500 mothers in the USA, Hendricks et al (25) observed that being in day care was associated with decreased duration of breastfeeding at ages 6 and 12 months.…”
Section: Day Carementioning
confidence: 99%
“…human _ ontogenetic s Introduction of a "Baby-Year", however, might not only affect the birth/death ratio. It is also likely to increase, e.g., the chance that a baby is breastfed, as a lower percentage of employed mothers start breastfeeding and the duration of breastfeeding is reduced among working mothers (Taveras et al 2003, Kim et al 2008. Besides a number of well-known short-term effects for mothers and infants, breastfeeding has benefi cial effects even for long-term health.…”
Section: Human _ Ontogenetic S G ü N T E R D ö R N E R E L K E R O mentioning
confidence: 99%